Effect of facemask use on cognitive function during a maximal running aerobic fitness test - Slimani, Maamer; Paravlic, Armin; Abazovic, Ensar; Znazen, Hela; Bragazzi, Nicola Luigi (Frontiers in Physiology, 2022)
Background: The aim of the present randomized, crossover study was to determine the physiological and cognitive function responses while wearing a facemask during a maximal running aerobic fitness test. Methods: Fourteen healthy, nonsmoking physical education students (age = 17.5 years, height = 1.72 m, body mass = 70.4 kg) volunteered to participate in this study. They carried out a 20 m multistage fitness test (MSFT) while wearing or not a cloth facemask on two separate occasions performed in random order. The “Rating of Perceived Exertion” (RPE) and the d2 test for visual attention were administered and assessed before and immediately after the MSFT for both conditions (with or without a facemask). Results: When wearing the facemask, the participants exhibited lower maximal aerobic speed (p = 0.039), VO2max (p = 0.039), distance covered during the MSFT (p = 0.057), and concentration performance (p < 0.001), when compared with the control situation (without facemask). Moreover, they made more errors compared with the control condition (p = 0.021). The use of a cloth facemask during maximal endurance running tests (such as the MSFT) reduced VO2max, and measures of cognitive performance as assessed by the test of focused visual attention (the d2 test). This data suggests avoiding using a cloth facemask during maximal aerobic fitness tests, and before any tasks that require a high level of visual attention.